Efficiency of Radiotherapy Treatment in Patients with Bone Metastases of Prostate Cancer and Renal-Cell Cancer (Eurasian Medical Research Periodical, 2022)
Data from the World Health Organization (WHO) show that about 4 million people worldwide experience pain every day due to malignant diseases; in half of these people, discomfort due to bone metastases is the dominant source of symptoms ( Pavlova N. S., Sergienko E. A., 2020; Radbruch L., 2020 ). Most patients with bone metastases develop severe pain as the disease progresses, resulting in a significant reduction in their quality of life. In recent years, there has been a steady increase in the incidence of malignant neoplasms in all major localizations. Unfortunately, there remains a high percentage of tumors detected in stage 4 of the process in the presence of distant metastases, including bone metastases. Bone metastases have a very bad impact on the patient's quality of life. In particular, bone pain is the most common type of pain caused by cancer, which may require opiate analgesics and palliative radiotherapy for pain